A Fair Share of Tax A Fiscal Anthropology of Contemporary Sweden - Björklund Larsen, Lotta (Springer International Publishing : Imprint: Palgrave Macmillan, 2018)
This book is open access under a CC BY 4.0 license. This book takes a taxpayer's perspective to the relations taxation creates between people and their state. Larsen proposes that in order to understand tax compliance and cheating, we have to look beyond law, psychological experiments and surveys to include tax collectors and taxpayers' practices. The text explores the view of taxes seen as citizen's explicit economic relation to the state and implicit economic relation to all other compatriots. Larsen suggests how to build and increase tax compliance if we take the idea of taxation creating reciprocal relations seriously. The empirical cases are based on ethnography from two opposing tax practices in Sweden. Firstly, from a study of analysts, auditors, legal experts and managers at the Swedish Tax Agency and how they, quite successfully, strive for legitimacy in their tax collecting activities in society. Secondly, from fieldwork among a group of middle-aged Swedes and how they justify their tax-cheating when purchasing work off the books. Sweden is a modern society seen as particularly rational and the least prone to worry about survival issues; they trust their government and fellow citizens. Sweden is therefore an important country to look at as an example of tax compliance and whether other countries showing a continuous inclination towards these values will follow their lead.